Predicting extreme rainfall over eastern Asia by using complex networks - 何苏红 封泰晨 龚艳春 黄雁华 吴成国 龚志强 (Chinese physics B, 2014)
A climate network of extreme rainfall over eastern Asia is constructed for the period of 1971-2000, employing the tools of complex networks and a measure of nonlinear correlation called event synchronization （ES）. Using this network, we predict the extreme rainfall for several cases without delay and with n-day delay （1 ≤ n ≤ 10）. The prediction accuracy can reach 58% without delay, 21% with 1-day delay, and 12% with n-day delay （2 ≤ n ≤ 10）. The results reveal that the prediction accuracy is low in years of a weak east Asia summer monsoon （EASM） or 1 year later and high in years of a strong EASM or 1 year later. Furthermore, the prediction accuracy is higher due to the many more links that represent correlations between different grid points and a higher extreme rainfall rate during strong EASM years.